Content Validity and Authenticity of the 2012 English Test in the Senior High School National Examination - Widyaningrum, Frisca Ayu Desi; Prabandari, Carla Sih (LLT Journal: A Journal on Language and Language Teaching, 2013)
This paper discusses content validity and authenticity of the English testitems in National Examination (UN) year 2012. It is worth discussion because UN,which was administered nationally, was the most important standardized test toassess Indonesian students competence. The study aimed to find out how valid thecontent of the English test items of National Examination year 2012 for senior highschools isand how authentic the English test items of National Examination year2012 for senior high schools is. The writers employed a qualitative research withdocument analysis to conduct the analysis of both content validity and authenticityof the English test items. The data were obtained from the document and analyzedby using checklists. Besides, to maintain the validitiy of the analysis, a triagulationwas done by distributing aquestionnaire to four experts in language assessment.There were twofindings resulted form the analysis. First, the content of the NationalExamination year 2012 was 98.8% valid since almost all of the contents wererelevant to the test specifications. However, there were three reading test versionswhich failed to represent kinds of texts, namely explanation text. Second, theNational Examination year 2012 met the criteria of authenticity with percentage79.5% since some listening and reading test items failed to conform to authenticitycriteria. Natural language use, the relevance of the test topics, and real-worldrepresentativeness became problematic aspects to meet the higher standard ofauthenticity.